Woord en beeld: Iemand had twee zonen (Lucas 15:11-32) - Gosker, Margriet (Acta Neerlandica, 2021)
As an ecumenical theologian I studied all my life the words of the Holy Scriptures. I am also interested in images, strengthening the power of expression of words and the Word, and the other way around. In our present time the culture of images seems to be more and more important. One image can tell you more in a minute than many words can do. The Bible is interpreted by many interpreters and preachers in books, sermons and meditations. How can images interpret these Bible Stories? It is a challenge to show the correlation between the words of the Bible and its images. In this essay, I focus on the parable of the prodigal son. It shows three personalities: the father and his two sons. This raises the question: what about the mother? What is the interference between this story and the way individual artists managed to shape it in paint, pencil, stone, woodcut, and other materials? The youngest son is a spoiler. His life is adventure and pleasure and he has no limits. The eldest son is responsible and obedient, but he also has his dark side. Both of them could be a question to us. With whom could we identify ourselves? Some artists in their finest imagination did not stick to the story and made images of the mother or even of a prodigal daughter.